Students' Perceptions of the Teaching Materials Used in the English for Tours and Travel Course - Armawan, I Ketut (Universitas Pendidikan Ganesha, 2023)
Teaching materials have a big role in facilitating student learning goals, both short-term and long-term, in producing graduates who comply with the standards described above. This research aims to analyze the perceptions of English Language Education Study Program students regarding the teaching materials used in the English for Tours and Travel course and the basic problems faced by course teachers in developing English for Tours and Travel teaching materials. This research includes descriptive research based on local wisdom. The subjects of this research were 42 people, consisting of 2 lecturers teaching the English for Tours and Travel course and 40 seventh-semester students in the English Language Education Study Program. Data collection methods in this research include questionnaires, interviews, and documentation. The data obtained was then analyzed using quantitative descriptive statistical analysis techniques by calculating the mean (M) and Standard Deviation (SD). From the results of document analysis, questionnaires, and interviews, it can be concluded that it is urgent to develop English for Tours and Travel teaching materials based on local wisdom.